Utilization of Artificial Intelligence in Combating Transnational Crimes Through the Indonesian Immigration System - Adhitya Graha Pratama; Margaretha Hanita; Basir . S (Journal of Business, Social and Technology, 2026)
Background: The rise of transnational crimes and digital technology challenges state security, while Indonesia’s limited resources and manual immigration systems hinder crime prevention efforts. Objective: This study aims to analyze the utilization of Artificial Intelligence (AI) in Indonesia’s immigration system as a strategic instrument for combating transnational crimes from the perspectives of international law and national resilience. Methods: The methodology employed in this study is a literature review, systematically examining reputable international journals, accredited national journals, and scholarly books discussing Artificial Intelligence, transnational crimes, international law, and immigration policies. The analysis applies a normative juridical and conceptual approach to assess the compatibility of AI applications with international legal instruments, such as the United Nations Convention against Transnational Organized Crime and the United Nations Convention against Corruption, as well as Indonesia’s national legal framework. Results: The novelty of this research lies in integrating Artificial Intelligence, international law on transnational crime, immigration functions, and national resilience into a unified analytical framework. AI is viewed not only as an administrative tool but also as a strategic component of national security through border monitoring, risk analysis, biometric identification, and predictive immigration intelligence. The study finds that AI can improve foreign national supervision, accelerate early detection of transnational crimes, and strengthen international cooperation, although its implementation still requires stronger legal frameworks, human rights protection, and clear accountability mechanisms. Conclusion: With an appropriate approach, Artificial Intelligence can serve as a strategic instrument to strengthen Indonesia’s national resilience through an adaptive, modern, and security-oriented immigration system.